The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10103-014-1706-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of LLLT on biomechanical properties of tibial diaphysis in two rat models of experimental osteoporosis by a three point bending test

Abstract: Osteoporosis (OP) is a disease which causes bone loss and fractures, leading to severe pain and deformity. This study has aimed to assess the effects of pulsed wave low-level laser therapy (PW LLLT) on cortical bone in two experimental models of OP in rats. There were four ovariectomized (OVX-d) groups and four dexamethasone-treated groups. The healthy group were considered for baseline evaluations. At 14 weeks following ovariectomy, the OVX-d rats were further subdivided into the following: control rats with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…However, some recent studies show that LLLT alone is not effective in reversing the detrimental effects of OP in vivo …”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies show that LLLT alone is not effective in reversing the detrimental effects of OP in vivo …”
Section: Introductionmentioning
confidence: 99%
“…The most important marker of osteoporosis is the severe decrease in bone strength, which directly results in bone fractures [45]. The three-point bending test has been commonly used to evaluate bone strength [46], which has shown that bending ultimate load, modulus of elasticity, energy to failure, and stiffness are good indicators of the mechanical load of cortical bone [47]. In this study, the results of the three-point bending test of tibial diaphysis showed that the administration of HEFF at a higher dosage to OVX animals produced a significant increase in bone strength.…”
mentioning
confidence: 99%
“…28 In the current study, the authors used sham and OVX rats, which are most commonly used as experimental and control animal models for postmenopausal OP, 29 and the duration from bilateral ovariectomization to the extraction, isolation, and culture of BMMSCs was 3.5 months. 24,25 This model has also been approved by the Food and Drug Administration to be the primary model system for preclinical evaluation of agents used for the prevention and treatment of postmenopausal OP. 30 BMMSC from postmenopausal women with OP showed significant decreases in cell growth, proliferative response, and osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The OVX rats were subjected to total ovariectomy. 24 OVX was carried out by two paravertebral skin incisions while the rats were under general anesthesia. The rats were anesthetized by intramuscular injections of 50 mg∕kg ketamine hydrochloride (Rotex Medica, Tritteu, Germany) together with 5 mg∕kg diazepam (Caspian, Rasht, Iran).…”
Section: Ovariectomymentioning
confidence: 99%